STRATEGIKOMUNIKASIBIJAKMEMILIHDALAM MEMBENTUKPEMAHAMANPEMILIHPEMULATERKAIT PEMILIHANPRESIDENDANPEMILIHANUMUMTAHUN2024 - Dewi Sekartaji, Audi; Lukmantoro, Triyono; Sunarto, Sunarto (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
As the majority of voters, the younger generation has not yet demonstrated readiness in voting due to a lack of knowledge about the contesting candidates and a general disinterest in politics.